AUTHORSHIP PATTERN & COLLABORATION IN ETRI JOURNAL: A SCIENTROMETRIC STUDY - Narzary, Richa; Murugan, C. (International Journal of Research -GRANTHAALAYAH, 2017)
This study aims to evaluate the publications in ETRI Journal during the year 2010-2016. The data were retrieved from the web of science database maintained by Thomson Reuters, analyzed using tools like HisCite and Microsoft Excel. The adopts various method like Relative growth rate, doubling time, Exponential Growth Rate, Average Authors per Paper, Degree of collaboration etc. focusing on various aspect of the journal such as document types, year wise distribution of publication, authorship pattern, authors productivity, institutions involved, relative growth rate, degree of collaboration, countries wise, most prolific authors of the journal and keyword wise distribution etc. The study reveals that ETRI journal has come out with 7volumes, 42 issues and total publications of 936 articles. The highest number of publications in terms of articles was in the year 2013 followed by 2012. The study shows that most of the papers (98.46%) were contributed jointly whereas (1.6%) papers were contributed by single authors. It reveals that Kim J is the most productive author contributing 58 (6.2%) of articles in ETRI journals. The country wise distribution shows that highest number of contribution comes from the South Korea itself a total record showing 656, (70.1%). ETRI itself is the top most contributors in ETRI Journal and the word “Based” is the most common key word used, with total of 228 (24.4%) records.